(untitled) (Aksioma Education Journal, 2025)
This study aims to analyze the influence of emotional intelligence on the mathematics achievement of senior high school students in Indonesia. A quantitative approach using Structural Equation Modeling with Partial Least Squares (SEM–PLS) was applied to 100 respondents selected through simple random sampling. The research instrument consisted of a five-point Likert-scale questionnaire measuring emotional intelligence and mathematics achievement. The results revealed that emotional intelligence has a positive and significant effect on mathematics achievement, with a coefficient of β = 0.524 and a p-value of 0.000. The R-Square value of 0.436 indicates that emotional intelligence explains 43.6% of the variance in students’ mathematics achievement. These findings imply that academic success in mathematics is not solely determined by cognitive intelligence but also by students’ abilities to regulate emotions, manage anxiety, and maintain learning motivation. The study highlights the importance of integrating emotional development into mathematics learning strategies to enhance students’ resilience and improve academic performance.